Reorganization of urban spaces in a mountain resort - Émeline Hatt (Revue de Géographie Alpine)
Fordist ski resorts must cope with internal and external pressures. These restrictions strain relations between the functional and symbolic rationale of the purpose-built resorts of the 1960-70s. In the larger context of a ‘return to local values’, increasing attention is being paid to the quality of the inhabited environment, even if only used for only short stays. To address the escalation of issues related to land coverage and landscape features, we need to ‘make do’ with the ski resort’s urban legacy, perceived as a (micro) territorial datum and a potential resource. The scenography of such mountain resorts is seen as a way of promoting micro-territorial resources. This research into the planning of tourist facilities focuses in particular on analysis of Gourette, a resort in the Pyrenees that chose to reorganise its urban spaces as part of a “requalification” project.